Upaya Fasilitator Puspaga Balai RW dalam Meningkatkan Motivasi Belajar Anak di Kelurahan Tanjung Perak - Luana Shiany Margareta; Binti Azizatun Nafi’ah (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research discusses the implementation of the counseling program at Puspaga Balai RW on children's learning motivation. The focus of this research is the efforts of Puspaga facilitators in carrying out their role to bring public services, namely counseling, closer to the community. The research method used is qualitative research with descriptive methods. The research subjects were residents who had used Puspaga RW Hall counseling services. Data collection through in-depth observation and interviews. The conclusion of this research is that the Puspaga Balai RW counseling service is able to provide positive changes to children's learning motivation.